MANAGEMENT BANDWIDTH PADA DYNAMIC QUEUE MENGGUNAKAN METODE PER CONNECTION QUEUING - Rifai, Bakhtiar (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
The acceleration of the use of the internet and the need for the allocation of bandwidth needed, a method that is used for the management of internet usage and bandwidth needs. A large number of hotspots – hotspot that allows many people to connect to the device so that it requires adequate bandwidth in use. Method per connection is a queueing method that divides a large number of users in a network with a bandwidth that is provided to share the same evenly to each connected user. Method per connection queue is particularly suitable in the application where the user in a network number is dynamical.